Functional MRI-guided microsurgery of intracranial arteriovenous malformations: study protocol for a randomised controlled trial. Issue 10 (23rd October 2014) - Zhao, Bing; Cao, Yong; Zhao, Yuanli; Wu, Jun; Wang, Shuo
Abstract : Introduction: Intracranial arteriovenous malformations (AVMs) are associated with high morbidity and mortality. Modern microsurgery has improved the results of surgical treatment of AVMs; however, the treatment of AVMs, particularly eloquently located AVMs, still carries a high risk. Functional MRI (fMRI) has been reported to be used for the preoperative evaluation of AVMs in small case series. The purpose is to identify the utility and efficacy of fMRI-guided microsurgery of AVMs in a large randomised controlled trial. Methods and analysis: The study is a prospective, randomised controlled clinical trial. This study will enrol a total of 600 eligible patients. These eligible patients will be randomised to the standard microsurgery group and the fMRI-guided microsurgery group in a 1:1 ratio. Patient baseline characteristics and AVM architecture and characteristics will be described. In the fMRI-guided group, fMRI mapping of an eloquent cortex in all AVMs will be identified. Surgical complications and outcomes at pretreatment, post-treatment, at discharge and at 1-month, 3-month and 6-month follow-up intervals will be analysed using the modified Rankin Scale (mRS). This trial will determine whether fMRI-guided microsurgery could improve outcomes in patients with AVMs and also identify the safety and efficacy of fMRI-guided microsurgery. Ethics and dissemination: The study protocol and written informed consent were reviewed and approved by the Institutional Review Board of Beijing Tiantan Hospital Affiliated to Capital Medical University (ky2012-016-02). Study findings will be disseminated in the printed media. Trial registration number: ClinicalTrials.gov NCT01758211 .